A secure multi-frequency resonator for printable chipless RFID tag based on multifractal planar geometry. Issue 12 (13th August 2019) - Chouchene, Wissem; Larbi, Chiraz; Aguili, Taoufik
ABSTRACT: In this paper, we are presenting a secure, compact and directly printable resonator for chipless RFID tag based on multifractal planar shape. The multifractal Cantor set shows an interesting performance of the monostatic radar cross section for chipless RFID tag. Unlike the classical RFID tag, where for each frequency a resonator is needed, so the number of resonators increases when the identification range increases, by using the Iterated Function System (IFS) the obtained resonator has many resonant frequencies leading to decreasing the number of resonators in chipless RFID tag. In addition, due to their auto similarities and multiscale resolutions resonant frequencies generated by the multifractal Cantor set are not independents: all resonant frequencies are correlated, so we cannot map a frequency peak to only one resonator, because the resonator itself represents a multi frequencies signature. These lead to a more secure tag, which is a challenge for many growing applications.